Identifying the Factors Affecting MSMEs’ Intention to Buy Flavor B2 Replacer as Halal Seasoning Solution - Ricky Setiawan Sulistyo; Masmira Kurniawati (University of Merdeka Malang, 2023)
Consumption of halal food is currently not only a concern of the Muslim community, but non-Muslim communities have also paid attention to halal products due to their high health orientation. Lard oil is one of the ingredients to improve the taste of food; however, besides being haram, lard contains quite a complex fat content, so all people with health problems cannot consume it. Various breakthroughs have been made by innovating new products, such as the development of artificial flavors that can produce taste characteristics similar to lard but are healthy and halal to consume. This article examines the factors that influence the interest in using food and beverage providers to replace lard with B2 replacer products based on halal awareness, halal food knowledge and perceived value with attitude as a mediating variable. By taking a sample of 372 MSMEs food and beverage providers in the DKI Jakarta area using a purposive sampling technique, this study found that perceived value is the most powerful factor influencing purchase intention, followed by the halal awareness factor. However, halal food knowledge was found to have no direct effect on purchase intention.